Comparison of the effects of high-dose atorvastatin and high-dose rosuvastatin on oxidative stress in patients with acute myocardial infarction: A pilot study - Celal Kilit; Fatma Emel Koçak; Türkan Paşalı Kilit (KARE Publishing, 2017)
Objective: Oxidative stress is increased in patients with acute myocardial infarction (AMI). Statins reduce oxidative stress independent of their effect in reducing low-density lipoprotein cholesterol (LDL-C). The aim of the present study was to compare the effects of atorvastatin and rosuvastatin on oxidative status by investigating serum paraoxonase, serum arylesterase, total oxidant status, total antioxidant status (TAS) and oxidative stress index (OSI) in patients with AMI. Methods: Seventy patients with AMI were randomized into 2 groups; total of 55 patients (19 females, 36 males) aged 32 to 86 years completed the study and were included in the analysis. Patients were treated with 80 mg atorvastatin or 40 mg rosuvastatin for 4 weeks. Lipid parameters and parameters of oxidative status were measured at admission and after 4-week statin treatment. Results: After 4-week treatment, atorvastatin and rosuvastatin were associated with significant reduction in TAS, OSI, total cholesterol, and LDL-C levels. Serum paraoxonase level was significantly increased in both groups, while high-density lipoprotein cholesterol (HDL-C) level was significantly reduced in atorvastatin group. No statistically significant differences were found between atorvastatin and rosuvastatin in terms of actual difference in oxidative stress parameters. Conclusion: Atorvastatin and rosuvastatin have similar effects on oxidative status in patients with AMI. Rosuvastatin affected HDL-C level more favorably than atorvastatin.